Isolation and characterization of a higher-copy-number mutant of plasmid R6K - Nesvera, J; Hochmannová, J (Folia microbiologica, 1983)
A stable copy-number mutant (pNH601) of plasmid R6K was isolated by selection for increased resistance to ampicillin determined by this plasmid. The size of the mutant plasmid was found to be unchanged (26 Mg/mol) but it is present in 27 copies of pNH601 per E. coli K-12 chromosome which represents a two-fold increase of R6K copy number value. The following genetic properties of pNH601 are reported and compared with those of R6K: conjugative transfer, fertility inhibition of plasmids belonging to other incompatibility groups, incompatibility with plasmid R485 under both non-selective and selective conditions and the integrative suppression of the dnaA ts mutation. The mutant plasmid pNH601 was found to be different from the original R6K in most of these properties.
Keywords: DNA bakterií; Escherichia coli; ampicilin; Mutation; konjugace genetická; mutace; R-plasmidy; Conjugation, Genetic; DNA, Bacterial; R Factors; kruhová DNA; streptomycin; Streptomycin; Ampicillin; DNA, Circular